Surveying domestic abuse victims: the inimical lack of common ground - Rebollo Couto, Léticia (The crime data handbook, 2024)
Owing to the complexity of domestic abuse, wherein a wide spectrum of behaviours can be subsumed, the subject has been studied in multiple fields (from health sciences to policing), and through different prisms (such as prevention, detection and response). However, there is no conceptual clarity nor agreement on how it should be analysed. Even when domestic abuse analysis is restricted to the criminal justice system - the main focus of this chapter - its definition may still differ between countries and between institutions within the same country. The first section of this chapter covers the current methodological difficulties of surveying domestic abuse victims, the survey measures developed to capture domestic abuse and how they affect results. The second section focuses on the lack of congruence in the surveys that are routinely applied to domestic abuse victims with purposes other than obtaining crime data – that is, victim satisfaction surveys. The chapter presents a critical overview of the different limitations of surveying domestic abuse victims, and how they can be overcome. Although the examples provided are from England and Wales, insights derived therefrom will hopefully be more far reaching.